The food preferences of five commercially important fishes of Gosthani estuary - Rao, L M; Sivani, G (Indian Journal of Fisheries, 2011)
The food and feeding habits of five species of commercially important fishesof the Gostham estuary (two mullets, one each of milk fish, sand whitings andsilver biddies I have been studied. They exhibited food preferences accordingto their habitats. However, at times they were found to encroach upon otherhabitats and feed on a variety of food materials. This kind of feeding habitmight have arisen because of the shallowness of the estuary, the depth of whichis less than a foot at many places.